Microvesicles Bind Soluble Fibrinogen, Adhere to Immobilized Fibrinogen and Coaggregate with Platelets - Holme, Pål André; Solum, Nils Olav; Brosstad, Frank; Pedersen, Turid; Kveine, Marit (Thrombosis and Haemostasis, 1998)
In the present study we have investigated whether platelet derived microvesicles can bind soluble fibrinogen, bind to immobilized fibrinogen, and coaggregate with platelets. Flow cytometry was used for studies on binding of soluble fibrinogen and coaggregation, whereas ELISA wells were used to study binding of microvesicles to immobilized fibrinogen. Biotinylated microvesicles produced by stimulation with A23187, thrombin or SFLLRN of platelets which had been surface-labelled with biotin, were used both for the coaggregation experiments and for the binding studies with immobilized fibrinogen. Unlabelled microvesicles and biotinylated fibrinogen were employed when studying binding of soluble fibrinogen to the microvesicles. For the flow cytometry, the biotinylated proteins were reacted with avidin or streptavidin which was PE-conjugated, whereas the same substances were conjugated with alkaline phosphatase for the ELISA studies. The microvesicles formed after stimulation of platelets by SFLLRN or A23187 clearly bound the soluble, biotinylated fibrinogen. Moreover, isolated biotinylated microvesicles added to washed platelets prior to activation, were associated to the microaggregates that formed after stimulation. A significant binding of biotinylated microvesicles to immobilized fibrinogen could also be detected. The binding of micro-vesicles to soluble and immobilized fibrinogen and association to platelets was clearly specific and at least partly dependent on the GPIIb-IIIa complex, as all of these phenomena could be prevented or reduced by addition of the c7E3 Fab which blocks the activated form of this receptor complex. From these in vitro results it is clear that microvesicles can bind to immobilized fibrinogen, bind soluble fibrinogen and are able to coaggregate with platelets. It may be speculated that these results also reflect a haemostatic role of microvesicles in vivo.